2022
DOI: 10.3389/fonc.2022.812224
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus in Burkitt Lymphoma in Africa Reveals a Limited Set of Whole Genome and LMP-1 Sequence Patterns: Analysis of Archival Datasets and Field Samples From Uganda, Tanzania, and Kenya

Abstract: Epstein-Barr virus (EBV) is associated with endemic Burkitt lymphoma (eBL), but the contribution of EBV variants is ill-defined. Studies of EBV whole genome sequences (WGS) have identified phylogroups that appear to be distinct for Asian versus non-Asian EBV, but samples from BL or Africa, where EBV was first discovered, are under-represented. We conducted a phylogenetic analysis of EBV WGS and LMP-1 sequences obtained primarily from BL patients in Africa and representative non-African EBV from other condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 63 publications
2
14
0
Order By: Relevance
“…While underdiagnosis and/or underascertainment of BL are possible explanations for the discrepant low BL rates in Asia, that explanation is inconsistent with the high rates for nasopharyngeal cancer [93] and extra-nodal NK/T-cell lymphomas [94], both associated with EBV, in Asia. The low BL rates could be an epidemiological manifestation indicating that EBV strains circulating in Asia have a lower population attributable risk for BL than EBV in Africa [63]. EBV phylogenetic data have confirmed that EBV in Asia is genetically distinct from EBV in Africa [63,[95][96][97].…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…While underdiagnosis and/or underascertainment of BL are possible explanations for the discrepant low BL rates in Asia, that explanation is inconsistent with the high rates for nasopharyngeal cancer [93] and extra-nodal NK/T-cell lymphomas [94], both associated with EBV, in Asia. The low BL rates could be an epidemiological manifestation indicating that EBV strains circulating in Asia have a lower population attributable risk for BL than EBV in Africa [63]. EBV phylogenetic data have confirmed that EBV in Asia is genetically distinct from EBV in Africa [63,[95][96][97].…”
Section: Discussionmentioning
confidence: 93%
“…EBV phylogenetic data have confirmed that EBV in Asia is genetically distinct from EBV in Africa [63,[95][96][97]. Moreover, the EBV in US/Europe is phylogenetically closer to that in Africa [63,96], which is intriguing given that BL rates in US/Europe intermediate to those in Africa versus Asia. Molecular analysis of EBV variants in regions with different BL rates could lead to discovery of EBV variants with differential risk for BL.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations